Ideologi Dakwah Anak dalam Lagu Islami Digital: Analisis Semiotika Roland Barthes pada Lirik ‘Bocah Cilik-cilik’ Cover Ulinnuha Official - Yusuf, Mochamad Aris (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
Islamic-themed children's songs distributed through digital media serve as both educational entertainment and a means of Islamic propagation. The song “Bocah Cilik-cilik,” published on Ulinnuha's official YouTube channel, has captured the attention of the Indonesian Muslim community because it combines local culture with values ​​that shape children's religious character. Therefore, this study uses a qualitative approach with Roland Barthes's semiotic analysis method. Data in the form of song lyrics are analyzed through three levels of meaning: denotation, connotation, and myth, to uncover the symbolic meaning and ideology of Islamic propagation. The analysis shows that at the denotative level, the song lyrics represent children's religious activities. At the connotative level, the song constructs idealized piety and religious behavior as normative values ​​for Muslim children. At the mythical level, the song constructs an ideological narrative that positions children as symbols of Islamic obedience and morality. These findings confirm that the Islamic propagation message in children's songs is not neutral but rather is imbued with ideology conveyed through cultural representations and digital media. Therefore, a critical study of the content of children's da'wah is important to understand the construction of meaning and the formation of collective consciousness of Muslim society in contemporary Indonesia.